Nano satellite: a new journey towards space science for Bangladesh - Md. Khalilur, Rhaman; Shakil, Shifur Rahman; Tarannum, Narzu (© 2016 Istanbul Technical University, 2016)
This report has been accepted by Istanbul Technical University but not published yet.